Colloidal Transport in Porous Media - Frimmel, Fritz H.; Kammer, Frank Von Der.; Flemming, Hans-Curt.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2007)
Colloids are known to be the often neglected phase for the transport of pollutants in aquatic ecosystems. The book covers the basics of abiotic colloid characterization, of biocolloids and biofilms, the resulting transport phenomena and their engineering aspects. The subject is presented from an international group of leading specialists devoted to colloidal sciences. The contributions include theoretical considerations, results from model experiments as well as field studies. The information given will serve students and scientists interested in the analytical, chemical, microbiological, geological and hydrological aspects of material transport in aquatic systems and soils.
Transport Phenomena -- Colloid Facilitated Transport in Natural Porous Media: Fundamental Phenomena and Modelling -- Influence of Na-bentonite Colloids on the Transport of Heavy Metals in Porous Media -- Colloid Transport Processes: Experimental Evidence from the Pore Scale to the Field Scale -- Transport of Colloids in Filter Columns: Laboratory and Field Experiments -- Biocolloids and Biofilms -- Colloid and Microbe Migration in Granular Environments: A Discussion of Modelling Methods -- Influence of Biofilms on Colloid Mobility in the Subsurface -- Subsurface Transport of Heavy Metals Mediated by Biosolid Colloids in Waste-Amended Soils -- Colloids and Contaminants, Engineering Aspects -- Ion - Colloid - Colloid Interactions -- Release of Contaminants from Bottom Ashes - Colloid Facilitated Transport and Colloid Trace Analysis by Means of Laser-Induced Breakdown Detection (LIBD) -- The Role of Colloid Transport in Metal Roof Runoff Treatment.
Keywords: Earth sciences; Analytical chemistry; Geochemistry; Hydrogeology; Geobiology; Microbiology; Earth Sciences; Geochemistry; Microbiology; Hydrogeology; Biogeosciences; Analytical Chemistry; Electronic books